INTELLECTUALIZATION OF GAS TRANSPORTATION CONTROL SYSTEM (Academicia Globe: Inderscience Research, 2022)
The article discusses the technology of fuzzy control, common among intellectual technologies. Fuzzy control is one of the promising ¬intelligent technologies that allow you to create high quality control systems. The advantages of such systems include: the possibility of using for complex processes when there is no simple mathematical model; expert knowledge about the control object or process can be formulated in verbal form; simplicity of structure; property of robustness or adaptability.The author believes that the use of intelligent technologies based on fuzzy logic provides a solution to a wide range of problems of robust and adaptive ¬control under uncertainty.